Parent–Adolescent Conflict as Sequences of Reciprocal Negative Emotion: Links with Conflict Resolution and Adolescents’ Behavior Problems - Moed, Anat (J Youth Adolesc, 2014)
Although conflict is a normative part of parent–adolescent relationships, conflicts that are long or highly negative are likely to be detrimental to these relationships and to youths’ development. In the present article, sequential analyses of data from 138 parent–adolescent dyads (adolescents’ mean age was 13.44, SD = 1.16; 52 % girls, 79 % non-Hispanic White) were used to define conflicts as reciprocal exchanges of negative emotion observed while parents and adolescents were discussing “hot,” conflictual issues. Dynamic components of these exchanges, including who started the conflicts, who ended them, and how long they lasted, were identified. Mediation analyses revealed that a high proportion of conflicts ended by adolescents was associated with longer conflicts, which in turn predicted perceptions of the “hot” issue as unresolved and adolescent behavior problems. The findings illustrate advantages of using sequential analysis to identify patterns of interactions and, with some certainty, obtain an estimate of the contingent relationship between a pattern of behavior and child and parental outcomes. These interaction patterns are discussed in terms of the roles that parents and children play when in conflict with each other, and the processes through which these roles affect conflict resolution and adolescents’ behavior problems.